2022
DOI: 10.3390/ijms23094974
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Alters the Immuno-Expression of Neuronal Nitric Oxide Synthase in the Rat Pancreas

Abstract: Nitric oxide is generated from nitric oxide synthase following hyperglycemia-induced oxidative stress during the course of diabetes mellitus (DM). We examined the temporal immuno-expression of neuronal nitric oxide synthase (nNOS) in the pancreas of diabetic and non-diabetic rats using immunohistochemical, immunofluorescence and western blot techniques 12 h, 24 h, 1 week, 2 weeks, 1, 8 and 15 months after induction of DM. nNOS co-localized with pancreatic beta cells but disappears 12 h after the onset of DM. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Asparaginase is also not expressed in the pancreas (https://www.proteinatlas.org/ENSG00000166183-ASPG). Several arginine metabolism pathways are not functional in healthy pancreas (e.g., enzymes arginine decarboxylase, arginase, and NO synthase), except for creatine synthesis pathway with proven expression of arginine:glycine amidinotransferase and guanidinoacetate N-methyltransferase (Emerald et al 2022;da Silva et al 2014). However, this pathway does not directly lead to mitochondrial oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Asparaginase is also not expressed in the pancreas (https://www.proteinatlas.org/ENSG00000166183-ASPG). Several arginine metabolism pathways are not functional in healthy pancreas (e.g., enzymes arginine decarboxylase, arginase, and NO synthase), except for creatine synthesis pathway with proven expression of arginine:glycine amidinotransferase and guanidinoacetate N-methyltransferase (Emerald et al 2022;da Silva et al 2014). However, this pathway does not directly lead to mitochondrial oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Other pathological conditions included an increased severity of obesity-related impaired glucose homeostasis, lipid metabolism disorder and reduced endothelial nitric oxide synthase phosphorylation, as reported in earlier studies. Nitric oxide synthase is an important molecule regulating endothelial function including blood flow and vascular integrity [ 114 , 115 ].…”
Section: Characteristics Of Adropin Knockout Micementioning
confidence: 99%
“…An interesting study on neuronal nitric oxide synthase (nNOS) expression in pancreatic islets was performed on a rat model. It revealed that nNOS levels in beta cells disappeared after 12 h from the onset of DM [ 52 ].…”
Section: Large Vessel Atherosclerotic Lesion In Dmmentioning
confidence: 99%